A Glitch In Photography - Kruyswijk, Anna Elisabeth (Revelar: Revista de Estudos da Fotografia e Imagem, 2016)
When thinking of Photography, the same rectangular shape pops into our minds. Notwithstanding how fixed and logical this may seem, 2151 century Photography has started to show signals that move away from its conventional format. The presence of Photography - in spatial, virtual and verbal ways - is being revisited. In many art practices today, participation and engagement play a role of increasing importance. For Photography as a form-bound practice the interaction with not only the eyes but also the body of the viewer is difficult. Contemporary experimental photographers tend to somewhat reject visual limitations due to paper size or screen format, and make space for the sudden and unexpected, both within and outside the photographic system. With the two artists Katharina Gaenssler (DE, 1974) and Rosa Menkman (NL, 1983) as case-studies, this article will show the integration of the uncertainty principle in the field of Photography. Here, manual craft and digital exploration cross paths in order to reach an updated body-brain achievement for Photography in agreement with our current times. Rather than standing still, the viewer is compelled to walk around in order to grasp not only the visual dimension of the photograph but also its level of impact. The work of the 2151 century photographer appeals to the body as sentimental.